2018
DOI: 10.18502/kss.v3i8.2502
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Islamic Financial Institutions in a Financial Crisis

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
1
0
Order By: Relevance
“…In a recent investigation conducted by Ayub et al (2023), it was established that riba (interest) yields detrimental effects on society, whereas ethical finance offers unique dimensions to enhance economic wellbeing. Notably, research has shown that Islamic banking establishments have played a role in promoting financial stability and resilience, particularly during times of global financial upheavals (Alrifai 2015;Bhatti and Bhatti 2009;Reno and Abdullah 2016;Setiawan 2018). The principles of risk-sharing, avoidance of interest (riba), and asset-based financing in non-riba loan systems have contributed to increased financial inclusivity, providing access to financing for small and medium-sized enterprises (SMEs) and individuals who were previously underserved (Shabsigh et al 2017).…”
Section: Dimensions Of Shari'ah Mode Financing and Quality Of Lifementioning
confidence: 99%
“…In a recent investigation conducted by Ayub et al (2023), it was established that riba (interest) yields detrimental effects on society, whereas ethical finance offers unique dimensions to enhance economic wellbeing. Notably, research has shown that Islamic banking establishments have played a role in promoting financial stability and resilience, particularly during times of global financial upheavals (Alrifai 2015;Bhatti and Bhatti 2009;Reno and Abdullah 2016;Setiawan 2018). The principles of risk-sharing, avoidance of interest (riba), and asset-based financing in non-riba loan systems have contributed to increased financial inclusivity, providing access to financing for small and medium-sized enterprises (SMEs) and individuals who were previously underserved (Shabsigh et al 2017).…”
Section: Dimensions Of Shari'ah Mode Financing and Quality Of Lifementioning
confidence: 99%
“…The validity of digitally signed documents is weakened by the use of manual stamps, requiring companies to obtain a digital stamp for digital signatures. Lastly, users face difficulties when verifying data (selfies), raising concerns about potential leaks of personal information (Setiawan, 2022). Privy's management infrastructure requires a clear overhaul that focuses on integrating strategy, execution, and analytics.…”
Section: Introductionmentioning
confidence: 99%
“…This is, of course, related to the costs incurred and the possible systemic impact. The use of imported raw materials used by companies in managing investments provided by Islamic banking is one of the causes of the negative response by Islamic banking (Setiawan, 2018). When the price of raw materials increases due to the depreciation of the rupiah, it will reduce the use of imported raw materials so that the investment capitalization value decreases.…”
mentioning
confidence: 99%